TVRI SUMSEL'S EFFORTS TO MAINTAIN THE EXISTENCE OF THE CHILDREN'S WORLD PROGRAM AMID THE SOCIAL MEDIA CURRENT - Lubna, Putri Piryal; Saputra, Sepriadi; Nurprameswari, Sonia (Journal of Innovative and Creativity, 2026)
TVRI South Sumatra's efforts to maintain the existence of the "Dunia Anak" program amidst the flow of social media. The method used is a qualitative approach with a case study, involving observation, interviews with key informants, and documentation analysis. The results of the study indicate that TVRI South Sumatra has adopted media convergence by using digital platforms such as YouTube to reach a wider audience. This program not only functions as entertainment, but also as an educational medium that actively involves parents and children. Despite facing challenges from other digital content, "Dunia Anak" has managed to maintain its relevance through content innovation and collaboration with educational institutions.